Determination of Performance Through Job Satisfaction: Competence, Motivation and Organizational Commitment at the Central Statistics Agency in West Sumatra - M. Afuan Afuan; Hapzi Ali; Zefriyenni Zefriyenni (Qubahan Academic Journal)
Specifically, this study aims to analyze how competence, motivation, and organizational commitment affect performance both directly and indirectly through job satisfaction. The sample consisted of employees at the Central Statistics Agency of West Sumatra Region, selected using the Slovin formula, obtained 269 samples that met the criteria, and the data were tested using SEM PLS3. The findings of the study revealed that competence, motivation, and organizational commitment each had a significant positive effect on job satisfaction. While competence showed a positive but insignificant effect on performance, motivation and organizational commitment had a significant positive impact on performance. In addition, job satisfaction significantly affected performance. Competence, motivation, and organizational commitment also significantly improved employee performance through job satisfaction. These results indicate that increasing competence, motivation, and organizational commitment significantly improved performance and job satisfaction, with job satisfaction mediating the relationship between these factors and employee performance. The results of this study emphasize the important role of competence, motivation and organizational commitment in improving overall employee performance. This study recommends that research subjects improve employee competence to improve their performance. This increase in competence is expected to enable the employees concerned to improve the process of achieving performance more effectively.